Plagiarism in Academic Texts - Rojas Porras, Marta Eugenia (2012)
The ethical and social responsibility of citing the sources in a scientific or artistic work is undeniable. This paper explores, in a preliminary way, academic plagiarism in its various forms. It includes findings based on a forensic analysis. The purpose of this paper is to raise awareness on the importance of considering these details when writing and publishing a text. Hopefully, this analysis may put the issue under discussion.